Forced migrants: Labour market integration and entrepreneurship - Güven Sak; Timur Kaymaz; Omar Kadkoy; Murat Kenanoglu (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In 2015, worldwide forced displacement was at its highest recorded level, surpassing 65 million. Out of this number, nearly 20 million people are those who fled their countries of origin to seek refuge in third countries. International responsibility sharing in terms of hosting the historical levels of refugee flows has so far been inadequate. Today, lower- and upper-middle income countries host 65 percent of the world's refugees, mostly in urban settings. Whereas refugee camps provide access to basic needs such as shelter, food and healthcare, displaced individuals living in urban settings have to sustain their needs through their own means. In turn, this requires access to labor market.
Keywords: J15; J61; 330; refugees; labour market; integration and entrepreneurship